Insights into bioactivity guided chemical profiling of Ziziphus jujuba Mill. fruits wild-growing in Montenegro - Tatjana Perović; Biljana Lazović; Mirjana Adakalić; Ana Džamić; Lazar Žarković; Uroš Gašić; Marina Kostić; Jovana Petrović; Dejan Stojković; Ana Ćirić (Heliyon)
Jujube (Ziziphus jujuba Mill.) is a highly abundant wild-growing plant in Montenegro. It has been utilized since old times for various bioactive properties by the natives, however its detailed chemical characterization, antimicrobial, antioxidant and cytotoxic potential have not been extensively explored. Herein, we used crud methanol extract and three fractions (methylene chloride, n-butanol and aqueous) to asses bioactive features of fruits from this wild growing edible plant, after which we performed the targeted analysis of phenolic compounds of n-butanol fraction by (UHPLC-DAD-MS/MS). Our antioxidant assays showed the highest radical scavenging potential for n-butanol fraction using DPPH and ABTS methods. As for the antimicrobial activity of extract and three fractions, generally aqueous showed the least promising antibacterial and antifungal properties, whereas methylene chloride, methanol and n-butanol fractions showed quite promising antimicrobial potential. E. coli and S. aureus strains were the most susceptible to the compounds present in the methylene chloride and n-butanol fractions with MIC of 0.01–0.025 mg/mL, and MBC 0.025–0.05 mg/mL, along with MRSA strain, which was the most susceptible to the effects of methanol extract with MIC of 0.10 mg/mL and MBC 0.15 mg/mL. The results of antifungal activity showed lower potential to inhibit growth of pathogenic fungi than bacteria, whereas cytotoxicity assay showed extracts have no effects towards HaCaT skin cell line.The n-butanol fraction had the overall most promising activity, and therefore was subjected to more in depth chemical analysis.